PROFESIONALISME PETUGAS UNIT PELAKSANA TEKNIS DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL - Ardiyanti, Desiska (Jurnal Ilmu Administrasi Negara, 2016)
Professionalism Officer Technical Implementation Unit Office of Population and Civil Registration. The research objective was to determine the technical professionalism of officers of the Department of Population and Civil Registration Bukitraya subdistrict in service to the community. The research approach is qualitative. The informants is Head of Unit, Head of Administration and Executive Staff. Data collecting technique is interview, observation and documentation. Analysis of data using an interactive model. The results showed that the professionalism of workers in the public services is still low. Factors that influence is because the officers do not understand tupoksinya well.